Artemisinin as an anticancer drug: Recent advances in target profiling and mechanisms of action - Wong, Yin Kwan; Xu, Chengchao; Kalesh, Karunakaran A.; He, Yingke; Lin, Qingsong; Wong, W. S. Fred; Shen, Han‐Ming; Wang, Jigang (Medicinal research reviews, 2017)
Artemisinin and its derivatives (collectively termed as artemisinins) are among the most important and effective antimalarial drugs, with proven safety and efficacy in clinical use. Beyond their antimalarial effects, artemisinins have also been shown to possess selective anticancer properties, demonstrating cytotoxic effects against a wide range of cancer types both in vitro and in vivo. These effects appear to be mediated by artemisinin‐induced changes in multiple signaling pathways, interfering simultaneously with multiple hallmarks of cancer. Great strides have been taken to characterize these pathways and to reveal their anticancer mechanisms of action of artemisinin. Moreover, encouraging data have also been obtained from a limited number of clinical trials to support their anticancer property. However, there are several key gaps in knowledge that continue to serve as significant barriers to the repurposing of artemisinins as effective anticancer agents. This review focuses on important and emerging aspects of this field, highlighting breakthroughs in unresolved questions as well as novel techniques and approaches that have been taken in recent studies. We discuss the mechanism of artemisinin activation in cancer, novel and significant findings with regards to artemisinin target proteins and pathways, new understandings in artemisinin‐induced cell death mechanisms, as well as the practical issues of repurposing artemisinin. We believe these will be important topics in realizing the potential of artemisinin and its derivatives as safe and potent anticancer agents.